Alchemy, the Vernacular, and Text Production in Late Medieval England: Presentation Strategies in Trinity College, Cambridge, MSS O.5.31 and R.14.37 - Grund, Peter J.; Norja, Sara (Taylor & Francis, 2026)
The article studies the strategies that late-medieval scribes used to present alchemical texts to their audience. Investigating two late fifteenth-century alchemical codices – Trinity College, Cambridge, MSS O.5.31 and R.14.37, both almost exclusively written in English – we demonstrate that the copyists took considerable pains to present reader-friendly texts. They provided neatly separated textual units, furnishing them with headings, manicules (pointing hands), and even a table of contents. This organisation is supported by the use of various ink colours, letter sizes, and framing devices. The appearance suggests significant pre-planning, perhaps even in a commercial context. We argue that these manuscripts highlight how readers engaged with alchemical texts and, by extension, that they reveal the importance afforded to texts and the vernacular as a vehicle for disseminating alchemical knowledge. In other words, it is not only the number of surviving manuscripts and their alchemical contents that are good indicators of late-medieval valuations of alchemy. Our study underscores how the visual materiality of extant textual artefacts also constitutes crucial evidence for our understanding of how practitioners used alchemical texts. It also exposes the place of alchemical texts in the text production industry of the time and illustrates the status of fifteenth-century alchemy more widely.